NOVEL PS-OME MIRNA130B-3P REDUCES INFLAMMATION AND INJURY AND IMPROVES SURVIVAL AFTER RENAL ISCHEMIA-REPERFUSION INJURY - Vazquez, Gustavo; Sfakianos, Maria; Coppa, Gene; Jacob, Asha; Wang, Ping (Shock (Augusta, Ga.), 2023)
Introduction : Acute kidney injury (AKI) is a prevalent medical disorder characterized by a sudden decline in kidney function, often because of ischemia/reperfusion (I/R) events. It is associated with significant chronic complications, and currently available therapies are limited to supportive measures. Extracellular cold-inducible RNA-binding protein (eCIRP) has been identified as a mediator that potentiates inflammation after I/R injury. However, it has been discovered that miRNA 130b-3p acts as an endogenous inhibitor of eCIRP. To address the inherent instability of miRNA in vivo , a chemically modified miRNA mimic called PS-OME miR130 was developed. We hypothesize that administration of PS-OME miR130 after renal I/R can lead to reduced inflammation and injury in a murine model of AKI. Methods : C57BL/6 male mice underwent renal I/R by clamping of bilateral renal hilum for 30 min or sham operation. Immediately after closure, mice were intravenously administered vehicle (phosphate-buffered saline) or PS-OME miR130 at a dose of 12.5 nmol/mouse. Blood and kidneys were collected after 24 h for further analysis. Separately, mice underwent renal I/R and administered vehicle or treatment and, survival was monitored for 10 days. Results : After renal I/R, mice receiving vehicle showed a significant increase in serum markers of kidney injury and inflammation including blood urea nitrogen, NGAL, KIM-1, and IL-6. After treatment with PS-OME miR130, these markers were significantly decreased. Kidney tissue mRNA expression for injury and inflammation markers including NGAL, KIM-1, KC, and MIP-2 were increased after renal I/R; however, these markers showed a significant reduction with PS-OME miR130 treatment. Histologically, treatment with PS-OME miR130 showed a significant decrease in neutrophil infiltration and injury severity score, and decreased apoptosis. In the 10-day survival study, mice in the treatment group showed a significant reduction in mortality as compared with vehicle group. Conclusion : In a murine renal I/R model, the administration of PS-OME miR130, a direct eCIRP antagonistic miRNA mimic, resulted in the reduction of kidney inflammation and injury, and improved survival. PS-OME miR130 holds promise to be developed as novel therapeutic for AKI as an adjunct to the standard of care.